PENGARUH KUALITAS PELAYANAN ADMINISTRASI DAN WAKTU PELAYANAN TERHADAP KEPUASAN PASIEN KLINIK DENTANITA - Nur Oktafiana Putri; Ari Apriani (Media Riset Bisnis Manajemen Akuntansi, 2026)
This study was conducted to assess how the quality of administrative services and speed of service affect patient satisfaction levels at the Dentanita Dokter Gigi Bersama Blora Clinic. This research applied a quantitative approach using a correlational method, where data collection was conducted using a Likert scale questionnaire (1–5) from 51 respondents and the data was analyzed using multiple linear regression through SPSS software. The research findings indicate that the quality of administrative services has a positive and significant effect on patient satisfaction, with an F value of 75.507 and a significance level of 0.001. Meanwhile, the R² value of 0.759 indicates that 75.9% of the variation in patient satisfaction can be explained by the quality of administrative services and service time. These findings are in line with the SERVQUAL model, which emphasizes the dimensions of reliability and responsiveness, and show that improving administrative services and time efficiency can increase patient satisfaction in regional dental clinics.Keywords: dental clinic, health services, patient satisfactio, quality of administrative services, service time.